Green extraction of high added value substances from spent coffee grounds: preliminary results - Georgieva, Sílvia S. (2018)
A supercritical fluid extraction (SFE) with pure CO2 and ethanol as a co-solvent (10 %) of spent coffee grounds was carried out at temperatures from 313 K to 333 K, pressures up to 40.0 MPa and the results obtained were compared with those of the conventional Soxhlet method using n-hexane as a solvent. The best extraction yield (12.0 %) was achieved by SFE with CO2+10 % ethanol, compared to 9.5 - 10.7 % by SFE with pure CO2 and 10.4 % with n-hexane. The antioxidant potential was evaluated by DPPH method and the best antioxidant activity was exhibited by the spent coffee oil obtained by SFE, CO2+10 % ethanol. The quantification and the identification of the oils composition were carried out by NMR. The main constituents of the extracted oils referred to the triacylglycerols (TAGs, 98.9 - 96.8 %). Minor amounts of 1,2 diacylglycerols (1,2 DAGs, 2.7 - 0.68 %), and the diterpenes cafestol (6.02 - 2.26 %), 16-O-methylcafestol (4.86 - 2.00 %) and kahweol (2.11 - 0.71 %), as well as caffeine (1.45 - 0.1 %), were also present in all the extracts.